2019
DOI: 10.1002/fsn3.1138
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant effect of Kimchi supplemented with Jeju citrus concentrate and its antiobesity effect on 3T3‐L1 adipocytes

Abstract: Citrus is cultivated throughout Jeju Island and is thought to possess some medicinal properties. Citrus concentrate is the most extensively utilized form of citrus in the food industry. In this study, antioxidant and antiobesity effects of Kimchi supplemented with citrus concentrate were investigated. Prepared Kimchi was infused with 7% citrus concentrate (CK) and freeze‐dried for analysis. Normal Kimchi (NK) without citrus concentrate was utilized as a control. Total phenol content (TPC), total flavonoid cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…FRAP in Korean commercial kimchi was approximately 39% higher than that in Chinese commercial kimchi (1956.56 and 1398.95 µM, respectively). In previous studies, most kimchi showed high antioxidant activity, which is deemed to be caused by a physiologically active substance in the ingredients [3,7]. Therefore, the observed difference in the antioxidant activities could be attributed to the differences in the physiological properties of the ingredients.…”
Section: Free Amino Acid Contents Of Commercial Kimchi Manufactured In Korea China and The United Statesmentioning
confidence: 93%
See 2 more Smart Citations
“…FRAP in Korean commercial kimchi was approximately 39% higher than that in Chinese commercial kimchi (1956.56 and 1398.95 µM, respectively). In previous studies, most kimchi showed high antioxidant activity, which is deemed to be caused by a physiologically active substance in the ingredients [3,7]. Therefore, the observed difference in the antioxidant activities could be attributed to the differences in the physiological properties of the ingredients.…”
Section: Free Amino Acid Contents Of Commercial Kimchi Manufactured In Korea China and The United Statesmentioning
confidence: 93%
“…Moreover, kimjang (making and sharing kimchi) was proudly listed in UNESCO's list of the intangible cultural heritage of humanity in 2013 [2]. Kimchi is commonly known to contain abundant nutrients and functional ingredients; and therefore, it exhibits various health benefits, including antioxidant [3][4][5], anti-obesity [6][7][8], anti-diabetic [9,10], and anti-cancer effects [11,12], among others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FRAP assay was carried out using a Total Antioxidant Capacity Assay Kit (A015–3-1) [ 34 ]. The FRAP working solution was prepared by mixing detection buffer, matrix fluid and substrate solution according to a 10:1:1 ratio.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, recent studies on the correlation between antioxidant transcription factors and COVID-19 found that the intake of kimchi, a representative Korean fermented dish, could alleviate COVID-19 symptoms by activating nuclear factor-erythroid 2-related factor-2 [ 3 , 4 ]. Other health benefits of kimchi, such as anticancer, anti-obesity, anti-diabetes, and antioxidant effects, have also been well established, and are closely associated with lactic acid bacteria (LAB) and LAB-derived bioactive substances [ 5 - 11 ].…”
Section: Introductionmentioning
confidence: 99%